Part II: Thermal analysis of naturally ventilated BIPV system: Modeling and Simulation - Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2018)
This is the second part of a two-part study based on the thermal behaviour of a naturally ventilated BIPV systems. In the first part an experimental analysis of the thermal behaviour of a naturally ventilated BIPV system is presented and two new correlations for the estimation of the convective heat transfer coefficients in the air gap between the PV panel and a second skin are given, for windy and non-windy conditions. The present study (second part) presents a simulation based thermal analysis of a naturally ventilated vertical BIPV system. The simulation model is created using the developed equations for the estimation of the convective heat transfer coefficients presented in the first part of the present study, and the model is validated with the use of experimental data shown in the first part as well. The experimental based correlations are imported in the mathematical model, in order to be able to investigate the effect of other parameters on the thermal behaviour of the system such as the height of the system, the size of the air gap and the air velocity in the duct. These parameters are not easy to be investigated experimentally and their investigation would be very time consuming. The simulation model has a good agreement with the experimental results. The results shown that an air gap of 0.1 m can create adequate air flow on naturally ventilated systems and can ensure low PV temperatures to avoid efficiency decrease. This can be done when the air gap has bottom and top openings to allow air circulation. In taller systems, the temperatures are higher and there is a drop of the efficiency of the system.
Keywords: BIPV; Natural ventilation; Photovoltaics; Thermal behaviour